Image enhancement technique using partial contrast stretching on abnormal Bone Marrow images for Leukemia screening - E. U., Francis; Mohd Yusoff, Mashor, Prof. Dr.; Azian Azamimi, Abdullah; Roseline, Hassan, Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.